Тепловая модель корпуса газотурбинного двигателя - Костюк, В. Е.; Кирилаш, Е. И. (НТУ "ХПИ", 2015)
Розроблено теплову модель корпуса ГТД, який є основним джерелом тепловиділення до простору укриття силового блока турбокомпресорного агрегата. Для підвищення адекватності моделі виконано ідентифікацію температур зовнішньої поверхні корпуса ГТД за їх експериментальними значеннями. Теплову модель корпуса ГТД можна використовувати для оцінки теплового стану обладнання силового блока.

Heat model of the gas-turbine case, which is the main source of the heat release into turbocompressor unit power block enclosure space, was developed. Identification of the gas-turbine case outer surface temperatures by their experimental values for model adequacy improvement was done. Gas-turbine case heat model can be used to power block equipment heat regimen estimation.
Gas-turbine case heat model
Keywords: турбокомпрессорные агрегаты; силовые блоки; тепловое состояние; граничные условия; жаровая труба; компрессор низкого давления